Low-cost high-stability hydrogen sulfide adsorbent and preparation method thereof

Through grinding, acid-base treatment and organic alcohol amine loading, low-cost and high-stability hydrogen sulfide adsorbents are prepared, which solves the problem of fragility of adsorbents in the prior art, and achieves efficient hydrogen sulfide adsorption performance and stability.

CN120242957APending Publication Date: 2025-07-04SINOPEC YANGZI PETROCHEMICAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410002600.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-02
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing hydrogen sulfide adsorbents are prone to shatter during transportation and use, causing the active components to fall off, affecting stability and service life, and are costly.

Method used

The activated carbon powder is ground by a planetary mill, and then treated with an acid or alkali solution, mixed with an organic alcohol amine and a binder, and then extruded and dried to form an adsorbent with mechanical strength.

Benefits of technology

The prepared adsorbent is cheap, simple and industrialized, has high adsorption performance and selectivity, and is not easy to break during transportation and use, and has excellent stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004644722190000071
    Figure BDA0004644722190000071
  • Figure BDA0004644722190000072
    Figure BDA0004644722190000072
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogen sulfide adsorption, and particularly relates to a low-cost high-stability hydrogen sulfide adsorbent and a preparation method thereof. The prepared adsorbent is low in price, simple in preparation process and convenient for industrial production. The organic alcohol amine is used as an active component, so that basic groups on the surface of the activated carbon are increased, and the adsorption performance and selectivity of the adsorbent are improved. Meanwhile, the adsorbent has relatively high mechanical strength, is not easy to break in the transportation and use processes, and has excellent stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen sulfide adsorption, and particularly relates to a low-cost and high-stability hydrogen sulfide adsorbent and a preparation method thereof. Background Art

[0002] Solid amine adsorbents have become an important research topic in the field of H2S adsorption due to their advantages such as high adsorption capacity, a large number of active sites, easy preparation, and regeneration process. The solid amine adsorbent loads organic amines in the pores of the porous carrier, and realizes the adsorption-desorption cycle of the adsorbent through the reversible reaction of H2S and amino groups. Commonly used carriers include mesoporous molecular sieves, activated carbon, metal-organic frameworks, and silica gel. The preparation methods mainly include the impregnation method and the grafting method. The impregnation method uses the principle of physical adsorption to support organic amines on the carrier, which is a relatively simple preparation process, and there are a large number of active sites on the adsorbent. On the other hand, the grafting method refers to the chemical reaction between a silane coupling agent with an amino group and the functional groups on the surface of the carrier to fix it in the pores. Due to the chemical action, the solid amine adsorbent prepared by the grafting method is more stable, but its preparation process is more complicated than the impregnation method, and the loaded active components are less than those of the impregnation method. Solid amine adsorbents can adsorb H2S at normal temperature and pressure, avoiding problems such as serious corrosion of equipment, easy foaming of the solution, and high energy consumption in the absorption method.

[0003] Jaiboon et al. (Fuel Processing Technology, 2014, 128: 276-282) prepared silica gel adsorbents modified with different types of amines and different amine contents by the impregnation method. Compared with other organic amines, polyethyleneimine has a higher amine density and can provide more active sites at the same loading amount. And an appropriate loading amount can ensure sufficient active sites on the surface of the carrier while avoiding the agglomeration of organic amines inside the pores and reducing the gas mass transfer resistance. Xue et al. (Journal of Industrial and Engineering Chemistry, 2012, 18(1): 169-173) prepared an adsorbent using N-methyldiethanolamine-modified mesoporous molecular adsorbent SBA-15 for removing a small amount of H2S gas in CH4. The loaded N-methyldiethanolamine did not change the ordered structure of SBA-15, but improved its H2S removal ability.

[0004] Most of the currently used hydrogen sulfide adsorbents are supported adsorbents. Loading basic groups on a suitable carrier can improve the dispersion of active components and increase the sulfur capacity of the adsorbent. The impregnation method is usually used to load the adsorbent. However, the adsorbent prepared by this method often breaks during actual transportation and use, resulting in the easy shedding of active components, which affects the stability and service life of the adsorbent. Therefore, developing a solid amine adsorbent with high adsorption activity, high stability and convenient for industrial application has high practical application value. Summary of the Invention

[0005] The purpose of the present invention is to improve the deficiencies of existing adsorbents and provide a preparation method of a hydrogen sulfide adsorbent with low cost and high stability. The specific steps of the present invention are as follows:

[0006] Step 1, grind the activated carbon to be treated into activated carbon powder.

[0007] Step 2, place the activated carbon powder obtained in Step 1 in an acidic solution for pickling, and then wash and dry it with water to obtain activated activated carbon; or place the activated carbon powder obtained in Step 1 in an alkaline solution for alkali washing, and then wash and dry it with water to obtain activated activated carbon.

[0008] Step 3, prepare an organic alkanolamine solution, and fully mix the prepared organic alkanolamine solution with a binder and the activated activated carbon obtained in Step 2 to obtain a plastic adsorbent mud.

[0009] Step 4, press and dry the plastic adsorbent mud obtained in Step 3 to form an adsorbent.

[0010] Among them, the grinding treatment in Step 1 is carried out by a planetary ball mill, the ball milling speed of the ball mill is 100 - 800 r / min, and the ball milling treatment time is 1 - 10 h. Preferably, the ball milling speed of the ball mill is 500 - 700 r / min, and the ball milling treatment time is 1 - 3 h.

[0011] The pickling conditions in Step 2 are as follows: the acidic solution uses hydrochloric acid, nitric acid, or sulfuric acid, the pickling time is 0.5 - 5 h, and the mass fraction of the acidic solution is 5 - 35 wt%; or the alkaline solution uses sodium hydroxide, ammonia water, or sodium carbonate, the alkali washing time is 0.5 - 5 h, and the mass fraction of the alkaline solution is 5 - 35 wt%. Preferably, pickling is carried out with nitric acid with a mass fraction of 30 wt% for 0.5 - 1 h.

[0012] The organic alkanolamine solution described in Step 3 is prepared by dissolving an organic amine in an ethanol solution. Among them, the organic amine is independently selected from ethanolamine, N-methyldiethanolamine, tert-butylaminoethoxyethanol, and polyethyleneimine; the binder is independently selected from starch and sesbania powder. Preferably, the organic alkanolamine solution is prepared by dissolving N-methyldiethanolamine in an ethanol solution, and the binder is sesbania powder.

[0013] The mixing method described in Step 3 is as follows: First, mix the activated activated carbon and the binder in a mass ratio of 20:1 to 3:1; then, mix them in a ratio of adding 4-6 g of the activated carbon-binder mixture per 10 ml of the organic alkanolamine solution; finally, add the mixed material to a planetary mixer and stir, with the mixer rotation speed being 100-500 r / min and the stirring time being 0.5-10 h. Preferably, first, mix the activated activated carbon and sesbania powder in a mass ratio of 5:1 to 4:1; then, mix them in a ratio of adding 4-6 g of the activated carbon-binder mixture per 10 ml of the organic alkanolamine solution; finally, add the mixed material to a planetary mixer and stir, with the mixer rotation speed being 300-500 r / min and the stirring time being 0.5-2 h.

[0014] The extrusion drying and forming process described in Step 4 is as follows: Use a rotary granulator to extrude the plastic adsorbent mud prepared in Step 3 through a sieve into particles, and obtain the formed adsorbent after drying; the aperture of the sieve is 1-5 mm, the drying temperature is 50-100 °C, and the drying time is 0.5-5 h. Preferably, use a rotary granulator to extrude the plastic adsorbent mud prepared in Step 3 through a sieve into particles, and obtain the formed adsorbent after drying; the aperture of the sieve is 3-5 mm, the drying temperature is 80-100 °C, and the drying time is 0.5-1 h.

[0015] Beneficial effects

[0016] The adsorbent prepared by the present invention is inexpensive, and the preparation process is simple, which is convenient for industrial production. The organic alkanolamine used in the present invention as an active component is beneficial to increasing the basic groups on the surface of the activated carbon and improving the adsorption performance and selectivity of the adsorbent. The adsorbent prepared by the present invention has relatively high mechanical strength and is not easily broken during transportation and use, and has excellent stability. Specific embodiments

[0017] Example 1: Preparation of Adsorbent 1

[0018] Step (1): Grinding activated carbon powder

[0019] Put a batch of activated carbon to be treated into a planetary ball mill and ball mill it at a speed of 200 r / min for 6 h to obtain activated carbon powder.

[0020] Step (2): Acid-activated activated carbon powder

[0021] Weigh 4 g of the activated carbon powder obtained in step (1) and place it in 100 ml of a 5 wt% hydrochloric acid solution for acid washing for 4 h. Then wash it with deionized water until neutral, and obtain the activated activated carbon after drying.

[0022] Step (3): Loading organic alkanolamine

[0023] Weigh 0.4 g of ethanolamine and dissolve it in 10 ml of ethanol (99 wt%) to prepare 10 ml of an ethanolamine solution; add 10 ml of the prepared ethanolamine solution, 4 g of the activated activated carbon obtained in step (2), and 0.2 g of starch to a planetary mixer, and mix well at 200 r / min for 8 h to obtain a plastic adsorbent mud.

[0024] Step (4): Extrusion drying and forming

[0025] Use a rotary granulator to extrude the plastic adsorbent mud obtained in step (3) through a sieve with a pore size of 1 mm into granules, and finally dry the obtained granules at 50 °C for 4 h to prepare adsorbent 1.

[0026] Example 2: Preparation of adsorbent 2

[0027] Step (1): Grinding activated carbon powder

[0028] Put a batch of activated carbon to be treated into a planetary ball mill and ball mill it at a speed of 600 r / min for 1 h to obtain activated carbon powder.

[0029] Step (2): Acid-activated activated carbon powder

[0030] Weigh 4 g of the activated carbon powder obtained in step (1) and place it in 100 ml of a 30 wt% nitric acid solution for acid washing for 0.5 h. Then wash it with deionized water until neutral, and obtain the activated activated carbon after drying.

[0031] Step (3): Loading organic alkanolamine

[0032] Weigh 1.6 g of N-methyldiethanolamine and dissolve it in 10 ml of ethanol (99 wt%) to prepare 10 ml of an N-methyldiethanolamine solution; add 10 ml of the prepared N-methyldiethanolamine solution, 4 g of the activated activated carbon obtained in step (2), and 0.8 g of sesbania powder to a planetary mixer, and mix well at 400 r / min for 1 h to obtain a plastic adsorbent mud.

[0033] Step (4): Extrusion drying and forming

[0034] Use a rotary granulator to extrude the plastic adsorbent mud obtained in step (3) through a sieve with a pore size of 4 mm into granules, and finally dry the obtained granules at 100 °C for 0.5 h to obtain adsorbent 2.

[0035] Example 3: Preparation of adsorbent 3

[0036] Step (1): Grind activated carbon powder

[0037] Put a batch of activated carbon to be treated into a planetary ball mill and ball mill it at a speed of 300 r / min for 2 h to obtain activated carbon powder.

[0038] Step (2): Acid-activate the activated carbon powder

[0039] Weigh 4 g of the activated carbon powder obtained in step (1) and place it in 100 ml of 20 wt% sulfuric acid solution for pickling for 2 h, then wash it with deionized water until neutral, and dry it to obtain activated activated carbon.

[0040] Step (3): Load organic alkanolamine

[0041] Weigh 1.2 g of tert-butylaminoethoxyethanol and dissolve it in 10 ml of ethanol (99 wt%) to prepare 10 ml of tert-butylaminoethoxyethanol solution; add 10 ml of the prepared tert-butylaminoethoxyethanol solution, 4 g of the activated activated carbon obtained in step (2), and 0.4 g of sesbania powder to a planetary stirrer and mix well at 300 r / min for 2 h to obtain a plastic adsorbent mud.

[0042] Step (4): Extrusion and drying for forming

[0043] Use a rotary granulator to extrude the plastic adsorbent mud obtained in step (3) through a sieve with a pore size of 2 mm into granules, and finally dry the obtained granules at 75 °C for 2 h to obtain adsorbent 3.

[0044] Example 4: Preparation of adsorbent 4

[0045] Step (1): Grind activated carbon powder

[0046] Put a batch of activated carbon to be treated into a planetary ball mill and ball mill it at a speed of 300 r / min for 2 h to obtain activated carbon powder.

[0047] Step (2): Alkali-activate the activated carbon powder

[0048] Weigh 4 g of the activated carbon powder obtained in step (1) and place it in 100 ml of 10 wt% potassium hydroxide solution for alkali washing for 3 h, then wash it with deionized water until neutral, and dry it to obtain activated activated carbon.

[0049] Step (3): Load organic alkanolamine

[0050] Weigh 1.0 g of tert-butylaminoethoxyethanol and dissolve it in 10 ml of ethanol (99 wt%) to prepare 10 ml of tert-butylaminoethoxyethanol solution; add 10 ml of the prepared tert-butylaminoethoxyethanol solution, 4 g of the activated activated carbon obtained in step (2), and 1.2 g of starch to a planetary mixer, and mix well at 400 r / min for 1 h to obtain a plastic adsorbent mud.

[0051] Step (4): Extrusion drying and forming

[0052] Use a rotary granulator to extrude the plastic adsorbent mud obtained in step (3) through a sieve with a pore size of 3 mm into granules, and finally dry the obtained granules at 60 °C for 3 h to obtain adsorbent 4.

[0053] Example 5: Preparation of adsorbent 5

[0054] Step (1): Grinding activated carbon powder

[0055] Put a batch of activated carbon to be treated into a planetary ball mill and ball mill at a speed of 200 r / min for 2 h to obtain activated carbon powder.

[0056] Step (2): Alkali activation of activated carbon powder

[0057] Weigh 4 g of the activated carbon powder obtained in step (1), place it in 100 ml of 5 wt% ammonia water solution for alkali washing for 4 h, then wash it with deionized water until neutral, and obtain activated activated carbon after drying.

[0058] Step (3): Loading organic alkanolamine

[0059] Weigh 1.6 g of polyethyleneimine and dissolve it in 10 ml of ethanol (99 wt%) to prepare 10 ml of polyethyleneimine solution; add 10 ml of the prepared polyethyleneimine solution, 4 g of the activated activated carbon obtained in step (2), and 0.8 g of starch to a planetary mixer, and mix well at 200 r / min for 3 h to obtain a plastic adsorbent mud.

[0060] Step (4): Extrusion drying and forming

[0061] Use a rotary granulator to extrude the plastic adsorbent mud obtained in step (3) through a sieve with a pore size of 2 mm into granules, and finally dry the obtained granules at 80 °C for 1 h to obtain adsorbent 5.

[0062] Example 6: Preparation of adsorbent 6

[0063] Step (1): Grinding activated carbon powder

[0064] A batch of activated carbon to be treated is placed in a planetary ball mill and ball-milled at a speed of 400 r / min for 2 h to obtain activated carbon powder.

[0065] Step (2): Alkali activation of activated carbon powder

[0066] Weigh 4 g of the activated carbon powder obtained in step (1), place it in 100 ml of a 30 wt % sodium carbonate solution, and wash it for 4 h. Then, wash it with deionized water until it is neutral, and dry it to obtain activated activated carbon.

[0067] Step (3): Loading organic alcohol amine

[0068] 0.8 g of N-methyldiethanolamine was weighed and dissolved in 10 ml of ethanol (99 wt%) to obtain 10 ml of N-methyldiethanolamine solution; 10 ml of the obtained N-methyldiethanolamine solution, 4 g of the activated carbon obtained in step (2), and 0.6 g of sesbania powder were added into a planetary mixer and mixed at 400 r / min for 6 h to obtain a plastic adsorbent slurry.

[0069] Step (4): Extrusion drying and molding

[0070] The plastic adsorbent sludge obtained in step (3) was squeezed into granules through a sieve with a pore size of 1 mm using a rotary granulator. Finally, the obtained granules were dried at 60° C. for 2 h to obtain adsorbent 6.

[0071] Comparative Example 1: Preparation of comparative adsorbent 1 (without organic amine loading treatment of the sample)

[0072] Step (1): Grinding activated carbon powder

[0073] A batch of activated carbon to be treated is placed in a planetary ball mill and ball-milled at a speed of 600 r / min for 1 h to obtain activated carbon powder.

[0074] Step (2): Acid activation of activated carbon powder

[0075] Weigh 4 g of the activated carbon powder obtained in step (1) and place it in 100 ml of a 30 wt % nitric acid solution for acid washing for 0.5 h, then wash it with deionized water until it is neutral, and dry it to obtain activated activated carbon.

[0076] Step (3): Preparation of plastic adsorbent slurry

[0077] 10 ml of ethanol (99 wt%), 4 g of activated carbon obtained in step (2), and 0.8 g of sesbania powder were added into a planetary mixer and mixed thoroughly at 400 r / min for 1 h to obtain a plastic adsorbent slurry.

[0078] Step (4): Extrusion drying and molding

[0079] The plasticizable adsorbent mud obtained in step (3) is extruded into particles through a 4-mm aperture sieve using a rotary granulator, and finally the obtained particles are dried at 100 °C for 0.5 h to prepare Comparative Adsorbent 1.

[0080] Comparative Example 2: Preparation of Comparative Adsorbent 2 (without acid activation treatment of the sample)

[0081] Step (1): Grinding activated carbon powder

[0082] A batch of activated carbon to be treated is placed in a planetary ball mill and ball milled at a speed of 600 r / min for 1 h to obtain activated carbon powder.

[0083] Step (2): Washing the activated carbon powder

[0084] Weigh 4 g of the activated carbon powder obtained in step (1), wash it with deionized water, and dry it to obtain activated carbon.

[0085] Step (3): Loading organic alkanolamine

[0086] Weigh 1.6 g of N-methyldiethanolamine and dissolve it in 10 ml of ethanol (99 wt%) to prepare 10 ml of N-methyldiethanolamine solution; add 10 ml of the prepared N-methyldiethanolamine solution, 4 g of the activated carbon obtained in step (2), and 0.8 g of sesbania powder to a planetary stirrer and mix well at 400 r / min for 1 h to obtain a plasticizable adsorbent mud.

[0087] Step (4): Extrusion drying and forming

[0088] The plasticizable adsorbent mud obtained in step (3) is extruded into particles through a 4-mm aperture sieve using a rotary granulator, and finally the obtained particles are dried at 100 °C for 0.5 h to prepare Comparative Adsorbent 2.

[0089] Comparative Example 3: Preparation of Comparative Adsorbent 3 (without organic amine loading treatment of the sample)

[0090] Step (1): Grinding activated carbon powder

[0091] A batch of activated carbon to be treated is placed in a planetary ball mill and ball milled at a speed of 400 r / min for 2 h to obtain activated carbon powder.

[0092] Step (2): Alkali activation of the activated carbon powder

[0093] Weigh 4 g of the activated carbon powder obtained in step (1), place it in 100 ml of 30 wt% sodium carbonate solution for alkali washing for 4 h, then wash it with deionized water until neutral, and dry it to obtain activated activated carbon.

[0094] Step (3): Prepare the plastic adsorbent mud

[0095] Add 10 ml of ethanol (99 wt%), 4 g of the activated activated carbon obtained in step (2), and 0.6 g of sesbania powder to a planetary mixer, and mix well at 400 r / min for 6 h to obtain the plastic adsorbent mud.

[0096] Step (4): Extrude and dry into shape

[0097] Use a rotary granulator to extrude the plastic adsorbent mud obtained in step (3) through a sieve with a pore diameter of 1 mm into granules, and finally dry the obtained granules at 60 °C for 2 h to obtain Comparative Adsorbent 3.

[0098] Comparative Example 4: Prepare Comparative Adsorbent 4 (without alkali activation treatment of the sample)

[0099] Step (1): Grind activated carbon powder

[0100] Put a batch of activated carbon to be treated into a planetary ball mill and ball mill at a speed of 400 r / min for 2 h to obtain activated carbon powder.

[0101] Step (2): Wash the activated carbon powder

[0102] Weigh 4 g of the activated carbon powder obtained in step (1), wash it with deionized water, and dry it to obtain the activated activated carbon.

[0103] Step (3): Load organic alkanolamine

[0104] Weigh 0.8 g of N-methyldiethanolamine and dissolve it in 10 ml of ethanol (99 wt%) to prepare 10 ml of N-methyldiethanolamine solution; add 10 ml of the prepared N-methyldiethanolamine solution, 4 g of the activated activated carbon obtained in step (2), and 0.6 g of sesbania powder to a planetary mixer, and mix well at 400 r / min for 6 h to obtain the plastic adsorbent mud.

[0105] Step (4): Extrude and dry into shape

[0106] Use a rotary granulator to extrude the plastic adsorbent mud obtained in step (3) through a sieve with a pore diameter of 1 mm into granules, and finally dry the obtained granules at 60 °C for 2 h to obtain Comparative Adsorbent 4.

[0107] Test example:

[0108] Test object: Use the adsorbent prepared in the present invention to remove trace hydrogen sulfide in the tail gas of coal gasification. Coal-derived syngas is one of the important methods for realizing the clean utilization of coal resources. The main component of the exhaust gas is CO2, and it also contains trace amounts of H2S (about 5 ppm). Without treatment, it will have an impact on the environment and equipment.

[0109] Test performance evaluation conditions: The performance of the adsorbent was evaluated using a fixed-bed adsorption device. The adsorbent was filled in a quartz tube, and both ends were fixed with glass wool. The inner diameter of the quartz tube was 9 mm, the particle size of the adsorbent was between 20 and 40 mesh, and the adsorption temperature was controlled by a high and low temperature constant temperature bath. The hydrogen sulfide concentration at the equipment inlet was 5 ppm, the reaction space velocity (WHSV) was 18,000 ml / g·h, and the adsorption temperature was 25 °C. The concentration of H2S at the outlet was detected by a GT930-F-H2S detector (measurement range 0 - 10 ppm; resolution 0.01 ppm, Shenzhen Korne Electronic Technology Co., Ltd.). According to the formula:

[0110]

[0111] The breakthrough adsorption capacity was calculated.

[0112] In the formula: Q t is the adsorption capacity, mg / g; C0 is the initial concentration of H2S, ppm; t is the adsorption time at the selected point, min; C(t) is the outlet concentration at time t, mg / m 3 ; q is the gas flow velocity through the adsorption column, L / min; m is the mass of the filled adsorbent, g.

[0113] The test results are shown in the following table:

[0114]

[0115] As can be seen from the above table, the breakthrough adsorption capacities of adsorbents 1, 2, 3, 4, 5, and 6 modified by acid activation, alkali activation, and organic amine loading for hydrogen sulfide are all about 3 mg / g, showing excellent H2S adsorption performance.

[0116] As can be seen from the results of Example 2 and Comparative Example 1, the breakthrough adsorption capacity of the adsorbent treated with organic amine loading for hydrogen sulfide increased from 1.127 mg / g to 3.996 mg / g; as can be seen from the results of Example 2 and Comparative Example 2, the breakthrough adsorption capacity of the adsorbent treated with acid activation for hydrogen sulfide increased from 1.168 mg / g to 3.996 mg / g. The results of the two groups of comparative tests show that the adsorption performance of the adsorbent treated with acid activation and organic amine loading has been significantly improved.

[0117] As can be seen from the results of Example 6 and Comparative Example 3, the breakthrough adsorption capacity of the adsorbent treated with organic amine loading for hydrogen sulfide increased from 1.233 mg / g to 3.898 mg / g; as can be seen from the results of Example 6 and Comparative Example 4, the breakthrough adsorption capacity of the adsorbent treated with alkali activation for hydrogen sulfide increased from 1.784 mg / g to 3.898 mg / g. The results of the two groups of comparative experiments show that the adsorption performance of the adsorbent treated with alkali activation and organic amine loading has been significantly improved.

Claims

1. A preparation method of hydrogen sulfide adsorption with low cost and high stability, characterized in that, The preparation steps are as follows: Step 1: Grind the activated carbon to be processed into activated carbon powder. Step 2: Place the activated carbon powder obtained in Step 1 in an acidic solution for pickling, and then wash and dry it with water to obtain activated activated carbon; Or place the activated carbon powder obtained in Step 1 in an alkaline solution for alkali washing, and then wash and dry it with water to obtain activated activated carbon; Step 3: Prepare an organic alkanolamine solution, mix the prepared organic alkanolamine solution with a binder and the activated activated carbon obtained in Step 2 to obtain a plastic adsorbent mud. Step 4: Press and dry the plastic adsorbent mud obtained in Step 3 to form an adsorbent.

2. The preparation method according to claim 1, characterized in that, In the grinding process described in Step 1, the ball milling speed of the ball mill is 100 - 800 r / min, and the ball milling time is 1 - 10 h.

3. The preparation method according to claim 1, characterized in that, The pickling conditions described in Step 2 are as follows: The acidic solution uses hydrochloric acid, nitric acid, or sulfuric acid, the pickling time is 0.5 - 5 h, and the mass fraction of the acidic solution is 5 - 35 wt%; or the alkaline solution uses sodium hydroxide, ammonia water, or sodium carbonate, the alkali washing time is 0.5 - 5 h, and the mass fraction of the alkaline solution is 5 - 35 wt%.

4. The preparation method according to claim 1, characterized in that, The organic alkanolamine solution described in Step 3 is prepared by dissolving an organic amine in an ethanol solution. Among them, the organic amine is independently selected from ethanolamine, N-methyldiethanolamine, tert-butylaminoethoxyethanol, and polyethyleneimine; the binder is independently selected from starch and sesbania powder.

5. The preparation method according to claim 1, characterized in that, The mixing method described in Step 3 is as follows: First, mix the activated activated carbon and the binder in a mass ratio of 20:1 - 3:1; then, mix them in a ratio of adding 4 - 6 g of the activated carbon-binder mixture per 10 ml of the organic alkanolamine solution; finally, stir the mixed material, the stirring speed is 100 - 500 r / min, and the stirring time is 0.5 - 10 h.

6. The preparation method according to claim 1, characterized in that, The extrusion drying and forming process described in Step 4 is as follows: Extrude the plastic adsorbent mud prepared in Step 3 through a sieve into particles, and after granulation, dry it to obtain a formed adsorbent; among them, the aperture of the sieve is 1 - 5 mm, the drying temperature is 50 - 100 °C, and the drying time is 0.5 - 5 h.

7. The preparation method according to claim 1, characterized in that, For the grinding treatment described in Step 1, the ball milling speed of the ball mill is 500 - 700 r / min, and the ball milling treatment time is 1 - 3 h; the pickling conditions described in Step 2 are: the acidic solution is nitric acid with a mass fraction of 30 wt%, and the pickling time is 0.5 - 1 h; the organic alkanolamine solution described in Step 3 is prepared by dissolving N-methyldiethanolamine in an ethanol solution, and the binder is sesbania powder; the mixing method described in Step 3 is: first, mix the activated carbon and sesbania powder in a mass ratio of 5:1 - 4:1; then, mix in a ratio of adding 4 - 6 g of the activated carbon-binder mixture per 10 ml of the organic alkanolamine solution; finally, stir the mixed material, with the stirring speed being 300 - 500 r / min and the stirring time being 0.5 - 2 h; the extrusion drying and forming process described in Step 4 is: extrude the plastic adsorbent mud obtained in Step 3 through a sieve into particles, and obtain the formed adsorbent after drying; wherein the aperture of the sieve is 3 - 5 mm, the drying temperature is 80 - 100 °C, and the drying time is 0.5 - 1 h.

8. The preparation method according to claim 1, characterized in that, For the grinding treatment described in Step 1, the ball milling speed of the ball mill is 600 r / min, and the ball milling treatment time is 1 h; the pickling conditions described in Step 2 are: the acidic solution is nitric acid with a mass fraction of 30 wt%, and the pickling time is 0.5 h; the organic alkanolamine solution described in Step 3 is prepared by dissolving N-methyldiethanolamine in an ethanol solution, and the binder is sesbania powder; the mixing method described in Step 3 is: first, mix the activated carbon and sesbania powder in a mass ratio of 5:1; then, mix in a ratio of adding 4.8 g of the activated carbon-binder mixture per 10 ml of the organic alkanolamine solution; finally, stir the mixed material, with the stirring speed being 400 r / min and the stirring time being 1 h; the extrusion drying and forming process described in Step 4 is: use a rotary granulator to extrude the plastic adsorbent mud obtained in Step 3 through a sieve into particles, and obtain the formed adsorbent after drying; wherein the aperture of the sieve is 4 mm, the drying temperature is 100 °C, and the drying time is 0.5 h.

9. A material prepared by the preparation method according to Claims 1 - 8.

10. The application of a material as described in claim 9, characterized in that, Use this material to remove trace hydrogen sulfide in the tail gas of coal gasification.